Social Capital Laundry Enterprises in Mailing Business Laundry in West Padang City Padang. - Syamrizal ramadhani; Afriva khaidir; Erianjoni (International Conference on Education, Islamic Studies and Social Sciences Research)
Padang City is a city of solid education will be a lot of services like Laundry. The entrepreneurs have social capital in maintaining the business that is run in Padang Barat Sub-district, Padang City. 1) The impact of social capital utilization. The type of research used qualitative research with descriptive method. Through the technique of selecting informants with purposive sampling. Data were collected by participant observation, interview, and documentation study methods. Analyzed by Miles and huberman Methods The business capital of laundry entrepreneurs in maintaining the laundry business by establishing: 1) activities such as laundry clothes. 2.The backlinks also have a very helpful role in making this enduring business known as symbiosis mutualism or mutual benefit.3.Trust or trust that addresses customer satisfaction in practical and efficient washing, especially padang city as the center of all activities.